Synthesis and properties of resorcin[4]arene based quadrupoles and dimeric electrostatic capsules - Atkins, Joseph (Kansas State University, 2009)
In the present study, the rescorcin[4]arenes decorated with an alternating arrangement of pyridinium and sulfonate moieties were synthesized to establish a molecular quadrupole. These rescorcin[4]arenes are capable of undergoing conformational changes from a ‘collapsed’ to ‘open’ state. The stability of the two state are controlled by the polarity of the solvent environment. The electrostatic interactions between pyridinium and sulfonates enforced a ‘quadrupolar collapse’ in solvents such as chloroform. While these interactions are disrupted in dimethylsulfoxide. A major synthetic challenge was functionalizing the resorcin[4]arene in a positive/negative/positve/negative pattern was successfully addressed. Comparison to dipolar resorcin[4]arene were undertaken to establish a quantitative measurement of the quadrupolar forces and to address the question of cooperatively provided addition attraction beyond two dipoles. A,C-functionalized-bis sulfonate resorcin[4]arenes and A,C function bis-pyridinium resocin[4]arenes were synthesized independently. Combining these dicationic and dianionic moieties provided an interdigitating dimeric unit with overall quadrupolar charge distribution. Disruption of the quadrupolar salt bridges in CDCl[subscript]3 was accomplished through the addition of DMSO or through dilution. DeltaG[superscript]o, DeltaH[superscript]o, and DeltaS[superscript]o have been determined for the dimer formation. Addition of pyridinium salts led to a disruption of the dimeric capsule. Host-guest binding studies established attractive binding to CS[superscript]2. Larger guests such as toluene, diiodobenzene, dicynanobenzene could not be encapsulated.
Keywords: Cavitands; Electrostatics; Quadrupoles; Capsule; Chemistry, Organic (0490)